Horseshoe crab genomes reveal the evolution of genes and microRNAs after three rounds of whole genome duplication - Wenyan Nong (Nature Portfolio, 2021)
Wenyan Nong, Zhe Qu, Yiqian Li, Tom Barton-Owen, Annette Wong and colleagues provide genomes and small RNA transcriptomes for the mangrove horseshoe crab and the tri-spine horseshoe crab. They show that horseshoe crabs have undergone three rounds of whole genome duplication and shed light on how gene families and microRNAS evolved following this genome duplication event.